La Realidad Aumentada como instrumento de innovación educativa para niños de 24 a 36 meses de edad - Flores Lagla, Galo Alfredo (2019)
The objective of this research is to develop educational didactic material applying augmented reality to strengthen cognitive learning and the children’s fine motor from 2 to 3 years old in the CDIs of the Eloy Alfaro parish in Latacunga, to achieve this objective, free software like Unity, Vuforia and Blender applications were used. The developed app consists of 2 sections that are related to the cognitive and motor areas. In the cognitive area 3 modules were developed, identified with: fruits, animals and professions, while the motor area was developed 2 modules identified with: farm animals and fruits, the image gallery is on the website http://jadelatacunga.site/. In addition, the evolutionary prototype software development model was used because it allows interaction with the requesting user until the final result is obtained, to validate the software, the expert judgment method was applied to experienced nursery school and computer professionals. Also, to evaluate the quality of the app, ISO / IEC 9126 quality standards were applied in regards to the criterion of Usability and Satisfaction, it was necessary to evaluate the use of the application with children, for which the checklist tool was used. The "before" and "after" practices of implementing the mobile application were carried out in the CDI "Little angels", obtaining the following results: more than 90% of the children who participated in the evaluation using the app managed to easily identify the animals, professions and fruits, that means that the app with augmented reality is fulfilling the proposed objective and therefore it is feasible to implement it in all the CDIs of Eloy Alfaro Parish in Latacunga canton.